Phase relations in the Tl2 Te–TlBiТe2 –TlTbTe2 system - Samira Z. Imamaliyeva; Ganira I Alakbarzade; Dunya M. Babanly; Marina V. Bulanova; Vagif A. Gasymov; Mahammad B. Babanly (Конденсированные среды и межфазные границы, 2021)
The phase equilibria in the Tl2Te–TlBiТe2–TlTbTe2 concentration area of the Tl–Bi–Tb-Te quaternary system were investigated by using the differential thermal analysis and powder X-ray diffraction techniques. The diagram of the solid-phase equilibria of this system at room temperature was constructed. It was established that the Tl9BiTe6–Tl9TbTe6 section divides the Tl2Te–TlBiТe2–TlTbTe2 system into two independent subsystems. It was found that the Tl2Te–Tl9BiTe6–Tl9TbTe6 subsystem is characterized by the formation of a wide field of solid solutions with a Tl5Te3 structure (d-phase) that occupy more than 90% of the area of the concentration triangle. The results of X-ray phase analysis of alloys of the Tl9BiTe6–Tl9TbTe6–TlTbTe2–TlBiТe2 subsystem showed the formation of wide regions of solid solutions based on TlTbTe2and TlBiTe2 along the section of TlTbTe2–TlBiTe2 ((b1- and b2 -phases) and made it possible to determine the location of the heterogeneous phase regions in this subsystem. The parameters of crystal lattices of mutually saturated compositions of the b1-, b2-, and d-phases are calculated from powder diffraction patterns. The paper also presents some polythermal sections, isothermal sections at 740 and 780 K of the phase diagram, as well as projections of the liquidus and solidus surfaces of the Tl2Te–Tl9BiТe6–Tl9TbTe6 subsystem. The liquidus surface consists of three fields of the primary crystallization of a (Tl2Te)-, d- and b1 -phase. The constructed isothermal sections clearly demonstrate that the directions of the tie lines do not coincide with the T–x planes of the studied internal sections, which is characteristic of non-quasi-binary polythermal sections. The obtained new phases are of interest as potential thermoelectric and magnetic materials.